Na semente já existe um baobá: capoeira, educação e transformação socioambiental - Ferrari, Maíra Miller (2018)
Every social experience produces and reproduces knowledge, this circle of actions presupposes one or more ​ epistemologies. Considering the current social-economic crisis it is essential to rethink the knowledge process and its connection with the reality consisted of the knowledgeable subject and the sensible object. On this matter, this thesis questions. For what reason has the hegemonic epistemology eliminated the cultural and political contexts of knowledge production and reproduction from its reflections? What are the consequences of this decontextualization?Are other epistemologies possible today?How to build knowledge despite the european thinking monopoly? Which are the possible contributions of Capoeira to establish other epistemologies valuing brazilian social and environmental reality and transforming it? We’ve tried to identify how capoeira, as a afro-brazilian social practice, can engender emancipatory educative processes which will contribute to the development of sustainable societies. A field research was developed at the Kilombo Tenendé, a ​ capoeira angola a ​ nd permaculture center, coordinated by master ​ Cobra Mansa and located in the city of Valença in Bahia State. Also at the ​ Corrégo do Mel ​ a research center of education, health and sustainability through ​ capoeira angola ​ , permaculture and spagyric, which is coordinated by master ​ Índio a ​ nd located in the São Gonçalo do Rio das Pedras, in Minas Gerais state. And finally at the ​ Associação de Capuêra Angola Paraguassú, c ​ oordinated by master Jaime from Mar Grande in Itaparica island, in the Bahia state. The results, analyses, and developments of the research are presented in the II part of this work through articles. The investigation is guided by the critical communicative methodology grounded in Paulo Freire’s and Junger Haberman’s theories. Guided by dialogue and assessments the work is a process built collectively by the researcher and all individuals involved in the researched contexts. Beyond observation, interpretation, description, and comprehension of the social and environmental reality we sought to transform it. We identified in the Capoeira universe educative processes grounded on the afro – brazilian knowledge diversity, therefore those are emancipatory processes since they arouse reflections on consumption, ethnic-racial relations, folk wisdom, food production, ancestral heritage, etc. Thus, these educative processes grounded in african epistemologies are fundamental to the ​ intentionality and ​ intelligibility of socially fair and environmentally sustainable societies.